(untitled) (The Review of Diabetic Studies, 2025)
Inflammation, internal organs, and neuropathies may all be alleviated or even prevented by cannabinoids When the central nervous system or the peripheral nervous system undergoes aberrant alterations, the outcome is chronic, non-adaptive pain, which is known as neuro-pathic pain. Typical analgesics have a terrible track record of relieving the symptoms of neuropathic pain. Although antineoplastic drugs are useful in chemotherapeutic treatment of malignant malignancies, they are also linked with significant adverse effects. Neuropathic pain induced by paclitaxel is well-documented to cause mechanical and thermal hyperalgesia, motor impairment, oxidative stress, and protein alterations, mimicking clinical chemotherapy-induced peripheral neuropathy. In our findings, treatment with the CB2 receptor agonist significantly improved pain threshold as evidenced by tail immersion latency, and enhanced sensory motor coordination and locomotor activity, indicating its role in modulating nociceptive signaling and motor functions. Similarly, dimethyl itaconate, a known anti-inflammatory and antioxidant molecule, restored behavioral parameters, suggesting a protective effect against paclitaxel-induced neurotoxicity. Biochemical analysis further demonstrated that both treatments reduced oxidative stress markers. DPPH assay confirmed improved free radical scavenging activity, while total calcium levels were significantly reduced, suggesting regulation of calcium homeostasis, which is otherwise disrupted in neuropathic states. Moreover, restoration of total protein content indicated neuroprotective effects, possibly through stabilization of structural and functional proteins. These results align with previous studies reporting the role of CB2 receptor modulation in attenuating neuropathic pain (and the antioxidant capacity of dimethyl itaconate in neuroinflammation The combined pharmacological and antioxidant findings suggest that CB2 receptor agonist and dimethyl itaconate act via complementary mechanisms—CB2 receptor activation reducing neuroinflammatory signaling, and dimethyl itaconate enhancing redox balance—to mitigate paclitaxel-induced neuropathic alterations